MeV single-ion beam irradiation of mammalian cells using the Surrey vertical nanobeam, compared with broad proton beam and X-ray irradiations - K. Prakrajang (2018)
As a part of a systematic study on mechanisms involved in physical cancer therapies, this work investigated response of mammalian cells to ultra-low-dose ion beam irradiation. The ion beam irradiation was performed using the recently completed nanobeam facility at the Surrey Ion Beam Centre. A scanning focused vertical ion nano-beam was applied to irradiate Chinese hamster V79 cells. The V79 cells were irradiated in two different beam modes, namely, focused single ion beam and defocused scanning broad ion beam of 3.8-MeV protons. The single ion beam was capable of irradiating a single cell with a precisely controlled number of the ions to extremely low doses. After irradiation and cell incubation, the number of surviving colonies as a function of the number of the irradiating ions was measured for the cell survival fraction curve. A lower survival for the single ion beam irradiation than that of the broad beam case implied the hypersensitivity and bystander effect. The ion-beam-induced cell survival curves were compared with that from 300-kV X-ray irradiation. Theoretical studies indicated that the cell death in single ion irradiation mainly occurred in the cell cycle phases of cell division and intervals between the cell division and the DNA replication. The success in the experiment demonstrated the Surrey vertical nanobeam successfully completed. © 2013 Elsevier B.V. All rights reserved.